Towards and understanding of the role of associative learning in risk for mental health problems - Byrom, N (2012)
The ability to prioritize information enables us to think and take action without being overwhelmed by external stimuli or internal thoughts and feelings. Neuroticism is associated with altered processing of emotional information but differences in the processing of emotional information may arise from basic differences in information processing, such as altered processes of attention, changes in sensitivity to salient information, or differences in the ability to encode conjunctions of information. Through this thesis, I explore the relationship between neuroticism and processing of non-emotional information, with a particular focus on learning about combinations of information. Associative learning paradigms were used to test ability to learn about combinations of information and neuroticism was observed to be associated with strong non-linear discrimination learning. The tendency to focus on specific details was associated with weak non-linear discrimination learning. A novel model of associative learning is presented, offering an account for how variation in the ability to engage in non-linear discrimination learning might be understood. Mechanisms underlying the association between neuroticism and strong non-linear discrimination learning were explored. Neuroticism was not found to be associated with a tendency to focus on specific details or shifts in attention towards goal relevant information. Neuroticism was not found to be associated with enhanced ability to identify feature conjunctions, altered sensitivity to the relative validity of stimuli or pre-exposure of stimuli. The importance of understanding individual differences in processes of associative and the value of associative learning tasks to look at information processing biases underlying neuroticism are discussed.